Pengaruh Kepercayaan, Harga dan Kemudahan terhadap Kepuasan Jemaah pada Biro Perjalanan Haji dan Umrah Kota Jambi - Akhmad Irwansyah Siregar; Riko Mappadeceng (Ekonomis: Journal of Economics and Business, 2020)
This research aims to analyze the influence of trust, price and ease on the consumer satisfaction of users of hajj and umrah travel agencies. The sample in this study is Jemaah on hajj and umrah travel agencies in Jambi city. Collection method using questionnaires and analyzed using verification analysis, analysis tools in research using Multiple Linear Regression, Determination Coefficient (R2), and F Test and tTest.